Current treatment options with immunoglobulin G for the individualization of care in patients with primary immunodeficiency disease. (2nd January 2015) - Jolles, S; Orange, J S; Gardulf, A; Stein, M R; Shapiro, R; Borte, M; Berger, M
Summary: Primary antibody deficiencies require lifelong replacement therapy with immunoglobulin (Ig)G to reduce the incidence and severity of infections. Both subcutaneous and intravenous routes of administering IgG can be effective and well tolerated. Treatment regimens can be individualized to provide optimal medical and quality-of-life outcomes in infants, children, adults and elderly people. Frequency, dose, route of administration, home or infusion-centre administration, and the use of self- or health-professional-administered infusion can be tailored to suit individual patient needs and circumstances. Patient education is needed to understand the disease and the importance of continuous therapy. Both the subcutaneous and intravenous routes have advantages and disadvantages, which should be considered in selecting each patient's treatment regimen. The subcutaneous route is attractive to many patients because of a reduced incidence of systemic adverse events, flexibility in scheduling and its comparative ease of administration, at home or in a clinic. Self-infusion regimens, however, require independence and self-reliance, good compliance on the part of the patient/parent and the confidence of the physician and the nurse. Intravenous administration in a clinic setting may be more appropriate in patients with reduced manual dexterity, reluctance to self-administer or a lack of self-reliance, and intravenous administration at home for those with good venous access who prefer less frequent treatments. Both therapy approaches have been demonstrated to provide protection from infections and improve health-related quality of life. Data supporting current options in IgG replacement are presented, and considerations in choosing between the two routes of therapy are discussed.